As new eyewitness of the barbarian impact on Spain - Frend, W. H. C. (Antigüedad y Cristianismo, 1990)
The recently discovered Divjak letters of St. Augustine have thrown new light on conditions in Tarragona in the early years of the barbarian invasions. While Hydatius and Paulus Orosius portray the horror of those times, a letter from a certain Consentius, resident in Minorca to Augustine (letter 11) leaves a different impression. Consentius had sent a monk, Fronto to the province to report on the activities of the priscillianists there. From Fronto's report it is clear that by 417 the interest of the populace was being stirred by religious faction. The barbarians though still feared had become little more than a nuisance, one more danger travellers must guard against. The return of relative peace provides a background to Orosius' optimistic hopes for a romano-gothic commonwealth that would restore the imperial grandeur of Rome. Consentius is an excellent witness to this interlude of hope before the final collapse of the empire in the west in the 430.